Poetry as moral education: representation of maternal love and gratitude in Miller Mottla’s “thank you Mom” - Naiborhu, Marlina Br; Sianipar, Mika Sonya; Bukit, Kyriena Hawila Br; Silitonga, Selomita Gracia; Hulu, Wien Warni Sari; Girsang, Martina (Indonesian Journal Education, 2026)
This study examines the representation of maternal love and gratitude in Miller Mottla’s poem Thank You Mom within the framework of literary analysis. The research aims to explore how intrinsic poetic elements construct emotional and ethical meaning in the text. Using a qualitative interpretative design, the study applies close reading to analyze key intrinsic components, including theme, diction, imagery, tone, and moral dimension. The findings reveal that maternal love is portrayed as a formative emotional force characterized by constancy, sacrifice, and moral guidance, positioning the mother figure as the central axis of the speaker’s identity formation. Gratitude emerges as the dominant thematic response, functioning not only as an emotional expression but also as an ethical recognition of relational influence. The analysis further demonstrates that linguistic simplicity enhances emotional accessibility and strengthens moral communicability, allowing the poem to convey universal values through direct expression. This study contributes to literary scholarship by challenging the assumption that poetic value depends primarily on structural complexity and by demonstrating that accessible poetic language can effectively function as a medium of moral education. The findings highlight the significance of poetry as both an aesthetic and pedagogical form capable of fostering emotional awareness and ethical reflection.